The Use of Products Recycled from Municipal Waste in Sustainable Architecture. (June 2019) - Iringová, A; Vandličková, D; Diviš, M
Abstract: Analysis of the use of products recycled from municipal and construction waste as a substitute of products from non-renewable sources. Current legislation on waste management in Slovakia. The process of manufacturing materials from recycled municipal waste and its environmental benefit to society. The products from recycled municipal and construction waste used in building constructions. Model verification of their application in building envelope construction. Their use as thermal, acoustic, and fire protection of wood-based buildings. Physical characteristics of model lightweight building envelopes assessed using mathematical and simulation solutions. Environmental comparison of a common solution for envelope construction with a solution using recycled waste products.